Modifikasi Algoritma El-gamal Dengan Menerapkan Algoritma Kargers Min Cut Untuk Pembangkitan Kunci - Ritonga, Rizki Darmawan (Jurnal Sains dan Teknologi Informasi, 2022)
El-gamal algorithm has two keys, namely public key and secret key. This algorithm has security that lies in the difficulty in calculating discrete algorithms. Both encryption and decryption keys are integers. El-gamal algorithm type asymmetric cryptography algorithm consists of two keys namely public key to encrypt while private key to decrypt. In El-gamal algorithms, distributed keys are public keys that are not required confidentiality while private keys remain stored or not distributed. Anyone who has a public key can do the encryption process but the result of that encryption can only be read by the person who has the private key. To increase the strength of the algorithm, the key used to perform the encryption and decryption process will be modified first using the randomization algorithm that is Karger Min Cut Algorithm. Karger Min Cut algorithm is a probabilistic random algorithm used to verify matrix multiplication. The purpose of using Kargers Min Cut algorithm is to make the resulting key more difficult to guess, making it difficult to read the message or information